Finite Element Study on the Preservation of Normal Knee Kinematics with Respect to the Prosthetic Design in Patient-Specific Medial Unicompartmental Knee Arthroplasty. (20th March 2020) - Koh, Yong-Gon; Park, Kyoung-Mi; Kang, Kyoung-Tak
Abstract : Alterations in native knee kinematics in medial unicompartmental knee arthroplasty (UKA) are caused by the nonanatomic articular surface of conventional implants. Technology for an anatomy mimetic patient-specific (PS) UKA has been introduced. However, there have been no studies on evaluating the preservation of native knee kinematics with respect to different prosthetic designs in PS UKA. The purpose of this study was to evaluate the preservation of native knee kinematics with respect to different UKA designs using a computational simulation. We evaluated three different UKA designs: a nonconforming design, an anatomy mimetic design, and a conforming design for use under gait and squat loading conditions. The results show that the anatomy mimetic UKA design achieves closer kinematics to those of a native knee compared to the other two UKA designs under such conditions. The anatomy memetic UKA design exhibited a 0.39 mm and 0.36° decrease in the translation and rotation, respectively, in the swing phase compared with those of the natural knee. In addition, under the gait and squat loading conditions, the conforming UKA design shows limited kinematics compared to the nonconforming UKA design. Our results show that the conformity of each component in PS UKA is an important factor in knee joint kinematics; however, the anatomy mimetic UKA design cannot restore perfect native kinematics.